ANALISIS PENGARUH BUDAYA ORGANISASI DAN ETIKA KERJA TERHADAP KINERJA KARYAWAN PERUSAHAAN PADA PT SAI INDONESIA CABANG SEMARANG - Dewi, Shara Kaprisa; Rodhiyah, Rodhiyah; Nugraha, Hari Susanta (Jurnal Ilmu Administrasi Bisnis, 2016)
Employee performance becomes a benchmark for the company's success in running the entire business activities. Performance was the result of the work of one's role in a particular task. Good employee performance can be seen from the achievement of the work in quality and quantity of employees. Appropriate organizational culture and a good work ethic will help in improving employee performance becomes better. This study aims to determine the influence of organizational culture and work ethic on the performance of the company's employees at PT SAI Indonesia Semarang branch. Explanatory research techniques, used census techniques (saturated sample) to 53 employees. The data obtained were analyzed qualitatively and quantitatively by means of testing the validity and reliability test. While data analysis is done using simple linear regression analysis, multiple linear regression, t-test and F test using SPSS. The results showed that organizational culture is at the very good category amounted to 67.9% and 32.1% good. The work ethic is at the very good category 54.7% but there is still 1.9% that is the category of no good. and the performance of employees is in the category of 60.3% excellent, 40% good and 5.7% is good enough. Besides, the organization's culture and work ethic significant influence on employee performance. Organizational culture has a weak influence on employee performance (9.7%) as well as the significant and positive impact on the performance of employees amounted to (0.023). The work ethic has a quite strong influence on the performance of employees (33.8%) as well as the significant and positive impact on the performance of employees (0,000). Organizational culture and work ethics have a strong influence on the performance of employees (34.4%). Conclusion: the overall culture of the organization and the work ethic and performance of employees in the company is at very good category but there are indicators that is still below the average value. Organizational culture and work ethic and positive significant influence on employee performance. It is recommended that the leader can provide guidance and coaching for employees as well as provide motivation and appreciate their work. Approaching to employees to play an active role in maintaining office equipment and providing training so that employees are more skilled and initiative work.